The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1200/jco.2015.62.4817
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of the HD2000 Trial Comparing ABVD Versus BEACOPP Versus COPP-EBV-CAD in Untreated Patients With Advanced Hodgkin Lymphoma: A Study by Fondazione Italiana Linfomi

Abstract: With these mature results, we confirm that patients with advanced Hodgkin lymphoma have similar OS results when treated with ABVD, BEACOPP, or CEC. However, with longer follow-up, we were not able to confirm the superiority of BEACOPP over ABVD in terms of PFS, mainly because of higher mortality rates resulting from second malignancies observed after treatment with BEACOPP and CEC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
65
2
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 28 publications
2
65
2
2
Order By: Relevance
“…These results are very encouraging as they show that interim PET allows a finely tuned treatment by restricting the use of BEACOPP to the 15% to 20% of patients who are PET-positive. BEACOPP offers higher cure rates in HL, but is also associated with a higher percentage of short-term and long-term adverse effects (hematologic toxicity, infections, infertility, secondary malignancies) [17]. In the absence of randomisation, the extent of benefit from switching to BEACOPP cannot be assessed from these trials [13,14].…”
mentioning
confidence: 99%
“…These results are very encouraging as they show that interim PET allows a finely tuned treatment by restricting the use of BEACOPP to the 15% to 20% of patients who are PET-positive. BEACOPP offers higher cure rates in HL, but is also associated with a higher percentage of short-term and long-term adverse effects (hematologic toxicity, infections, infertility, secondary malignancies) [17]. In the absence of randomisation, the extent of benefit from switching to BEACOPP cannot be assessed from these trials [13,14].…”
mentioning
confidence: 99%
“…The long-term follow-up analysis of the HD2000 trial also showed that the risk of secondary malignancy at 10 years was significantly higher with BEACOPP than with ABVD (6.7 vs 0.9; P =.027). 83 The ongoing EORTC 20012 trial is evaluating BEA-COPP (4 cycles of escalated-dose and 4 cycles of standard-dose) and ABVD (8 cycles) in high-risk patients with stage III–IV disease and an IPS of 3 or greater (274 patients in the BEACOPP arm and 275 patients in the ABVD arm). 81 The preliminary results showed no improvement in OS (86.7% and 90.3, respectively, at 4 years; P =.208) or EFS (63.7% and 69.3%, respectively, at 4 years; P =.312), although the PFS was significantly better with BEACOPP (83.4% vs 72.8% for ABVD; P =.005).…”
Section: Treatment Guidelinesmentioning
confidence: 99%
“…72 The long-term followup analysis of the HD2000 trial also showed that the risk of secondary malignancy at 10 years was significantly higher with BEACOPP than with ABVD (6.6 vs 0.9; P=.027). 76 Several trials have addressed the role of consolidative RT after completion of chemotherapy in patients with stage III-IV disease.…”
Section: Stage Iii-ivmentioning
confidence: 99%